Public perceptions as a potential barrier for prison reform in Panama: An analysis of user comments on YouTube - Sotelo, Mahaleth (International journal of comparative and applied criminal justice, 2024)
While the Constitution of Panama is remarkably progressive in regard to the treatment of incarcerated persons, the actual conditions faced by these individuals are frequently described as inhumane. We collected data from comments on YouTube videos displaying media on Panamanian prisons to investigate public opinion about their condition. We conducted a content analysis of comments, and use regression models to analyse their attitude, engagement (likes and replies) and the displayed characteristics of commenters. We found that comments tended to reflect a negative view of incarcerated individuals, either justifying bad conditions or asking for treatment that is more punitive. These negative comments also received the most engagement, and had commenters who were less mindful of their anonymity, indicating social desirability. We conclude that public opinion is itself a key barrier for prison reform which could account for the gap between legal prescriptions and the actual conditions of incarcerated individuals in Panama.